Impact of transient truck and train traffic on ambient air and noise levels in underserved communities. (August 2018) - Han, Inkyu; Samarneh, Lara; Stock, Thomas H.; Symanski, Elaine
Highlights: Air and noise pollution in underserved communities were measured. Effect of truck/rail traffic in communities nearby industrial facilities was examined. Trains and trucks passing nearby elevated air particulate matter (PM) and noise levels. Both PM and noise should be simultaneously measured for accurate exposure assessment. Abstract: Traffic-related air and noise pollution on or near major roadways have been examined but these pollutants have not been extensively investigated away from major roadways in residential communities, especially in the United States. To evaluate the impact of trucks and trains passing nearby on air and noise pollution in residential areas during non-rush hours, we simultaneously measured concentrations of size-resolved airborne particulate matter (PM) and sound pressure levels as A-weighted equivalent (dBA) with frequencies in three underserved communities adjacent to industrial facilities in Houston, TX. We found that median concentrations for PM1 (particle size ≤ 1 µm) and PM10 (particle size ≤ 10 µm) were highest when trucks passed by at sampling locations, followed by periods when trains passed by. PM1 and PM10 concentrations were lowest at background (defined when there was no truck or train traffic near the monitoring location). Median PM2.5 (particle size ≤ 2.5 µm) mass concentrations were 19.8 µg/m 3 (trains), 16.5 µg/m 3 (trucks), and 13.9 µg/m 3 (background). Short-term increases in noise were attributed to trains and trucks passing nearby as well. The median noise levels were the highest when trains passed by (66.7 dBA) followed by periods when trucks were in the vicinity of the monitoring locations (62.5 dBA); background levels were 58.2 dBA. The overall Spearman correlation coefficients between air and noise pollution were between 0.09 and 0.46. Hence, we recommend that both air pollutant and noise levels be concurrently evaluated for accurate exposure assessment related to traffic sources in residential communities.